FRI0472 Detection of Left Ventricular Morphology and Myocardial Abnormalities Using Contrast Cardiac Magnetic Resonance Imaging at 3.0 Tesla in Systemic Sclerosis Without Cardiac Manifestations. (9th June 2015) - Sugiyama, K.; Kobayashi, H.; Kobayashi, Y.; Nagasawa, Y.; Ikumi, N.; Nozaki, T.; Inomata, H.; Shiraiwa, H.; Karasawa, H.; Kitamura, N.; Iwata, M.; Matsukawa, Y.; et al.
Abstract : Background: Systemic sclerosis (SSc) has an increased prevalence of cardiac involvement despite often being clinically silent. When clinically evident, cardiac involvement decreased the 70% 5-year mortality of SSc. Cardiac magnetic resonance imaging (CMR) is useful in SSc beause it focuses on late gadolinium enhancement (LGE) abnormalities and ventricular morphology and function. Objectives: We aimed to assess the prevalence of subclinical myocardial involvement by left ventricular (LV) function and structure on CMR. We evaluated the relation between myocardial abnormalities and LV geometry. Methods: This study compared consecutive female SSc patients without cardiac symptoms and healthy female controls with no history or clinical findings of systemic and pulmonary hypertension by echocardiography, coronary artery disease, valvular heart disease, atrial fibrillation, diabetes mellitus, and dyslipidemia. All underwent non-contrast or contrast CMR on a 3.0-T scanner. LV function was measured using ejection fraction (EF), end-systolic volume (ESV), end-diastolic volume (EDV), stroke volume (SV), and cardiac output (CO). LV hypertrophy was measured by absolute LV mass (LVM) and LVM index (LVMI) determined by LVM/body surface area. LGE was obtained to assess myocardial fibrosis. Myocardial inflammation was assessed by black- blood T2WI. Serum BNP concentrations were measured simultaneously. Results: There were 44 SSc patients with a mean age of 57.1±8.7 years; 20 had diffuse type and 24 had limited type. There were 20 healthy controls with a mean age of 56.9±3.1 years. There were no significant differences in terms of age, gender, and cardiovascular risk factors. Compared with the control, SSc patients had a significantly higher EDV with tendency towards a high LVMI. There was no difference in EF. LGE (+) was detected in 25 of 44 (57%) SSc patients; LGE was in a linear pattern without coronary distribution in 13 (52%) SSc patients. T2WI was observed in 11 of 44 (25%) SSc patients. There were no differences in LGE and T2WI between the diffuse and limited type. The BNP level of the SSc group was significantly higher than that of the control group (P=0.04). The mean BNP level of SSc patients with LGE was significantly higher than that of SSc patients without LGE (P<0.0001). BNP level in SSc patients was significantly correlated with LVMI (P<0.0001) but not correlated with EF. Eccentric hypertrophy was observed in 52% of LGE (+) patients. LGE (+) was correlated with (+) anti Scl-70 antibody (P=0.004). After adjustment for age, disease duration, anti Scl-70 antibody, and BNP, SSc with LGE did not have a modified association with LVMI. Conclusions: SSc patients without cardiac symptoms have a high prevalence of cardiac abnormalities. Our data suggest that SSc-specific autoimmunity against Scl-70 mediates these changes. SSc patients with LGE had cardiac abnormalities associated with LVMI and serum BNP, leading to cardiac remodeling and possible development of cardiac involvement, even with a normal EF. Disclosure of Interest: None declared